PELATIHAN MEMBACA KITAB KUNING DENGAN METODE KITAB MUSTAQILLI - Suci Rahmawati; Ahmad Yani; Yeyet Nurhasanah; Rahmatullah (UI Cirebon (Universitas Islam Cirebon), 2023)
KKM students make one program, namely holding Fiqh book recitations which are held 2 times a week to provide knowledge about the science of fiqh. The recitation was well received by the community, the youth and even the children were very enthusiastic about participating in the recitation. The book we use is the Book of Safinatunnajah. The Mustaqilli method is a fast method of mastering Arabic, both in reading books, translating books, writing, composing, and speaking in Arabic. This method is deliberately structured with a simple concept, not complicated but very comprehensive. The Mustaqilli method is very different from the books or methods of existing teaching materials, the Mustaqilli method is an integrated system between simplified Arabic rules (Nahwu, Shorof) with exercises that are the key to success in learning Arabic. The results obtained during the training on how to quickly read the yellow book with the Mustaqilli book method, namely the children began to be able to mention the isim dzomir / pronoun in Arabic, know and be able to mention mufrodat (vocabulary) Arabic, can read language texts Arabic correctly and according to the rules of the Arabic language.